Externally Applied Metaphyseal Locking Plate: An Alternative to Unilateral External Fixator in Definitive Management of Compound Tibia Fractures - A Prospective Study - Supratim Roy; Kiran Wandile; Aliasger Moaiyadi; Akshay Rode; Bhavesh Patidar; CM Badole (Journal of Orthopaedic Case Reports)
Introduction: Compound tibial fractures are a common injury due to high velocity trauma and its management is always a challenge to the surgeon due to increased chances of infection, non-union, poor blood supply, and potential risk of amputation. Unilateral external fixator, though the gold standard, had many problems related to patient compliance and complications, such as joint stiffness. We aim to evaluate the effectiveness of the metaphyseal locking plate applied as an external fixator in managing the compound tibia fracture. Materials and Methods: We treated 16 cases of tibia fractures (proximal, diaphyseal, distal) with soft tissue injury using a metaphyseal locking plate as an external fixator and followed them for a period of 9 months to assess fracture union, complication, functional outcome, and patient compliance. Regular ankle knee range of movement was done and radiographs were taken to assess union and alignment of the limb. Results: The mean time to bony union was 19.7 weeks and the standard deviation is 5.75. Two cases of non-union, 3 cases of malunion, and 11 cases of union in proper alignment were achieved. 11 patients had excellent (68.75%), 2 had good functional results (12.5%), 1 had a fair functional outcome (6.25%), and 2 cases had poor functional outcome (12.5%). Conclusion: Metaphyseal locking plate can be an effective alternative to unilateral external fixator in terms of patient compliance, achieving good knee-ankle range of motion, fracture union, and thereby achieving good functional outcome.